ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KEPATUHAN WAJIB PAJAK ORANG PRIBADI PADA PELAKU USAHA MIKRO KECIL MENENGAH (UMKM) DI KELURAHAN TLOGOMAS KOTA MALANG - Johanis Nifanngeljau; Hermi Sularsih (Jurnal Akuntansi Trisakti, 2020)
The role of any tax is very important for a country's economic growth. Taxes constitute half of the role of the state and the active role of citizens and other members of the community to finance various state needs including national development and its implementation as stipulated in the objective law for the welfare state (Judisseno, 1997). The purpose of this study is to understand taxpayer awareness, understand taxes, and pay taxes with the approval of individual taxpayers. The problem in this study relates to the awareness of taxpayers, understanding taxes, valuing taxes and service quality related to individual taxpayer obligations. This type of research in this study is quantitative, the method used is a sampling method with a sample of 29 people. Characteristics of male gender respondents 55.2%, S1 education 24.1% while for age 29 years 17.2%. The calculation results of the Taxpayer Awareness variable have a t count of 0.562 with a significant level of 0.678, Tax Comprehension has a t count of 5.451 with a significant level of 0,000, the variable increase and protect memi t count by 12,015 with Tax Sanctions having a t count of 0.393 significant at 0.445, while Service Quality variable has a t count of 1.835 with a significant level of 0.079. Everything can be summed up as a significant Tax Understanding variable on individual taxpayer regulations, while the taxpayer awareness variable, tax understanding and service quality are not related to individual taxpayer obligations.